Verification of two methods of railway noise propagation - GOŁĘBIEWSKI, Roman; MAKAREWICZ, Rufin (Archives of Acoustics, 2009)
The noise maps of agglomerations comprise those of road traffic-, tram-, aircraft-, industrial- and railway noise. EU recommends the use of a few selected calculation methods for the estimation of noise: for road traffic noise - NMPB-Routes-96, for aircraft noise - ECAC.CEAC Doc 29, for industrial noise - ISO 9613-2 and for railway noise - Reken en Meetvoorschrijft Railverkeerslawaai 1996 (for tram noise - there is no specific computation method). However, the Member States can use their own computations methods provided that these methods have been positively verified. The results of the calculations using their own method and interim method must be compatible. In this paper, two methods of railway noise propagation are compared: the first one recommended by EU and the second one developed at the Adam Mickiewicz University in Poznań. The results obtained by the two methods are similar.